Interplay of spin, phonon, and lattice degrees in a hole-doped double perovskite: Observation of spin-phonon coupling and magnetostriction effect - Pal A.; Anand K.; Patel N.; Das A.; Ghosh S.; Yen P.T.-W.; Huang S.-M.; Singh R.K.; Yang H.D.; Ghosh A.K.; Chatterjee S. (My University, 2025)
Unlike a typical spin-phonon coupling, an exhibition of unconventional spin-phonon coupling, which is mediated via magnetostriction effect, is reported in a hole-doped double perovskite Pr1.5Sr0.5CoMnO6. Various investigations including electronic and crystal structures, spin structure, transport property, lattice dynamics, and theoretical density of states analysis by density-functional theory (DFT) have been performed. A substantial increase in the mean oxidation states of Co ions and a concurrent abrupt decrease in the resistivity upon Sr doping is observed, thus altering its underlying transport mechanism. An insulating and ferromagnetic (FM) ground state is predicted by DFT calculations. The neutron diffraction data analysis reveals a complex crystal structure of Pr1.5Sr0.5CoMnO6, which consists of B-site disordered monoclinic (P21/n) and orthorhombic (Pnma) structures, highlighting the presence of an anti-site disorder in the system. The analysis also suggests an overall FM ordering of Co/Mn spins below 150 K for the monoclinic phase, whereas no such magnetic ordering is found for the orthorhombic phase. More interestingly, the neutron powder diffraction study perceives the presence of a strong magnetostriction effect in the system. Raman spectroscopy unravels the presence of a spin-phonon coupling, which is essentially mediated by the magnetostriction effect. © 2022 Author(s).